Staging in the treatment of chronic calculous cholecystitis, complicated by choledocholithiasis - Alexander V. Smirnov; Vladimir R. Stankevich; Dmitry V. Sazonov; Artur R. Akhmedianov; Aishe A. Keshvedinova; Nikolay A. Solovyev; Yury V. Ivanov; Robert I. Khabazov (Клиническая практика)
BACKGROUND: Chronic calculous cholecystitis is the most widespread disease in scheduled surgery departments, which in 10–15% of observations is complicated by choledocholithiasis. As of today, the commonly acknowledged staged treatment tactics includes first an endoscopic lithoextraction, later followed by the laparoscopic cholecystectomy, with the durations of performing the latter not being defined. AIM: To define the optimal timings of performing the laparoscopic cholecystectomy after an endoscopic lithoextraction in cases of chronic calculous cholecystitis, complicated by choledocholithiasis. METHODS: The research included patients with chronic calculous cholecystitis, complicated by choledocholithiasis, which during the period of 2016–2023 years have received surgical aid at the Federal State Budgetary Institution “Federal Scientific and Clinical Center” of the Federal Medical-Biological Agency of Russia (n=87). Simultaneous endoscopic lithoextraction and laparoscopic cholecystectomy were carried out in 20 patients; 19 patients were operated within a single hospitalization with undergoing endoscopic lithoextraction and in 3 days — laparoscopic cholecystectomy (early cholecystectomy); in 48 patients laparoscopic cholecystectomy was delayed by 1–2 months after the endoscopic lithoextraction (interval cholecystectomy). RESULTS: When comparing the treatment results in three groups of patients, no statistically significant differences were observed, however, in the group of interval cholecystectomy, a tendency was shown for increasing the surgery duration, the conversion rate and the number of complications. CONCLUSION: In patients, not having signs of severe course of the disease, it is possible to perform simultaneous endoscopic lithoextraction and laparoscopic cholecystectomy. In the absence of complications, the applicable options include early (within 3 days) conducting the laparoscopic cholecystectomy, which does not worsen the results, however, it alleviates the necessity of repeated hospitalization and, probably, slightly decreases the risk of complications.